Energy Security of People’s Republic of China – Western dimension - Marcin Misiągiewicz (Facta Simonidis, 2013)
Central Asia is becoming more significant politically and economically because of its geopolitical position in Eurasia. It probably contains some of the largest undeveloped oil and gas reserves in the world. After the collapse of the Soviet Union, the newly-independent Central Asian states became open to foreign investments. The region can play an important role in the diversification of oil and gas supplies and consequently in global energy security. There are many external actors that want to be active and influential in Central Asia’s energy geopolitics. China is one of the most prominent players. Its growing energy needs have given it a strong interest in developing ties with the energy-producing states in the region. It participates in energy infrastructure projects to find opportunities to get access to oil and gas resources.